Focused Cardiac Ultrasound to Detect Pre-capillary Pulmonary Hypertension - Lyssens, Aurélie; Lekane, Marine; Gommeren, Kris; Merveille, Anne-Christine (Frontiers in Veterinary Science, 2022)
Background Early recognition of pre-capillary (PC) pulmonary hypertension (PH) benefits dogs, allowing earlier treatment and improving prognosis. The value of focused cardiac ultrasound (FCU) to diagnose PH and assess its severity has not been investigated yet. Hypothesis A subjective 10-point FCU pulmonary hypertension score (PHS) allows diagnosis and assessment of severity of PCPH. Animals This study involved fifty client-owned dogs. Methods Dogs, recruited between September 2017 and February 2020, were classified into four categories (no, mild, moderate, and severe PH; C1 to C4, respectively). C1 and C2, and C3 and C4 were regrouped as group 1 and group 2, respectively. A blinded general practitioner assessed four FCU cineloops. Five echocardiographic parameters were subjectively scored, resulting in a total score of 0–10. Non-parametric tests compared global scores between categories and groups. A receiver operating characteristic (ROC) curve determined the cutoff value to differentiate group 1 and group 2. A gray zone approach allowed diagnosing or excluding moderate to severe PH with 90% certitude. Results Global scores were significantly higher for C4 than for C1, C2, and C3. Global scores of G2 were significantly higher than G1. The ROC curve indicated a cutoff value of 5, discriminating group 1 from group 2 with a sensitivity of 77% and a specificity of 100%. A score of ≥5/10 allowed diagnosing moderate to severe PH with ≥90% certainty while a score of ≤2/10 excluded PH with ≥90% certainty. Conclusions and Clinical Significance Moderate to severe PCPH can be accurately detected by non-cardiologists using a 10-point FCU PHS score.